Pengaruh Pendidikan Keuangan, Pendapatan Keuangan, Literasi Keuangan dan Inklusi Keuangan terhadap Pengelolaan Keuangan UMKM di Kota Surabaya - Firmadhani, Fian; Sriyono, Sriyono (Universitas Batanghari Jambi, 2025)
This research examines the relationship between financial education, income, financial literacy and financial inclusion on the financial management of MSMEs. A purposive sampling approach was used in conjunction with quantitative methods. Data collection in the form of a questionnaire via Google Form. The research sample consisted of 100 participants. Multiple linear regression analysis and general assumption testing are two methods of data analysis. The results of this research reveal that simultaneously there is a positive and significant influence between the variables of financial education, income, financial literacy and financial inclusion on financial management variables. Meanwhile, literacy and financial inclusion variables are the variables that have the most dominant influence on the financial management of MSMEs in the city of Surabaya.